THE ROLE OF FAMILY, SCHOOL, AND ENVIRONMENT IN THE STRENGTHENING OF CHARACTER EDUCATION OF ELEMENTARY SCHOOL STUDENTS IN CENTURY 21 (International Conference on Elementary Education, 2018)
The 21st century is a century full of big leaps. This is shown by developments in almost all fields, especially science and technology. The development of science and technology has an impact like a double-edged knife. Can be useful, it can also hurt. Likewise the progress of science and technology, can be positive, it can also be negative. One of the negative impacts of technology abuse is the rise of student violations, such as social violations, immorality, promiscuity. This happens also for elementary students. Quoted from Suara.com August 6, 2018 five elementary school children in Depok were arrested by the police because of a brawl. One example of the many violations of elementary school children. This is a proof of imbalance between character and technological progress. In addition, the lack of optimal role and supervision of families, schools and the environment is a factor supporting elementary school children to commit violations. The next generation of the nation as a form of struggle to make improvements should be given a solid foundation with character education. Parents, teachers, environment have an important role in strengthening character education to deal with the 21st century multidimensional crisis.